Property maintenance management at Kuala Lumpur Tower / Mohd Fadzli Md. Rasid ... [et al.] - Md. Rasid, Mohd. Fadzli; Syid Abdullah, Syed Hazlan Izham; Ramsjah, Asma' Oz Zahrah Razali; Ramsjah, Hadijah; Mahmood, Haslina; Zakarya, Ruzila (2006)
The tower consists of five basic sections, namely the foundation base, the touristic building, the tower shaft, the tower head and the antenna mast. However patrons will have access to the touristic building, the observation platform and the revolving restaurant only.